Molecular pharming of consensus dengue viral envelope glycoprotein domain III in planta and its immunogenicity profiles in BALB/c mice - Pang, Ee Leen (2018)
Dengue fever has emerged as one of the fastest growing health problems in recent years. Transmission of the mosquito-borne disease is widespread throughout the tropics, causing intriguing effects to the poorer populations with limited access to healthcare. At present, most vector control programmes have failed to contain the disease and no specific treatment is available yet. The existence of dengue virus as four distinct serotypes poses a significant threat as secondary infection is often manifested in a more severe form leading to hospitalisation and even death. Hence, this pushes the demand for a dengue vaccine as a long-term protective approach. Particularly for developing nations, cost is a major factor that needs to be meticulously addressed in order to provide a quick yet affordable medical relief. With that, this study aimed at producing a safe and cost-effective plant-based dengue subunit vaccine to protect against the febrile illness. A consensus sequence of the dengue envelope glycoprotein domain III (namely cEDIII) was selected as the antigenic determinant. cEDIII was expressed in two forms, i.e. as recombinant proteins with fusion to green fluorescent protein (sGFP) or cholera toxin B subunit (CTB), and as an epitope display on hepatitis B core antigen (HBcAg) virus-like particles (VLPs). All the constructs were cloned into pEAQ-HT vector and transient expression was achieved via agroinfiltration of Nicotiana benthamiana plants. Following the successful detection of heterologous proteins in N. benthamiana, purification procedures were carried out to harvest the recombinant proteins and chimeric HBcAg VLPs-displaying cEDIII, correspondingly. The recombinant fusion of cEDIII to CTB was shown to preserve the ability to fold into its active pentamer and bind with native gangliosides. Meanwhile, assembly of the chimeric HBcAg VLPs-displaying cEDIII was verified via transmission electron microscopy. These purified recombinant proteins and chimeric VLPs were then used for immunogenicity testing in BALB/c mice. Following vaccination with the recombinant protein, the results showed that successful production of anti-cEDIII specific response with neutralising potency against four dengue serotypes was obtained. T cell analyses suggested that the cEDIII induced a predominant T helper (Th) 1 response while the fusion with CTB could skew the response towards a mixed Th1/Th2. Immunisation with the chimeric VLPs-displaying cEDIII also achieved induction of cEDIII-specific responses, however, further evaluations are needed to warrant the successful use of these VLPs-based vaccines. Overall, the findings in this study have provided solid evidence that the development of a plant-based dengue vaccine is feasible. This is of crucial importance to battle against the upsurge of disease burden, and the production of a local vaccine could complement with Malaysian government’s efforts in combating dengue disease.